The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.5958/0976-5506.2018.00646.0
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Rural Medical Internship: The Impact on Health Service and the Future Workforce

Abstract: Background: Studies have shown a shortage of medical practitioners in rural areas, and that graduate doctors are reluctant to practice in the rural areas. To address this shortage and reluctance, the Government of Indonesia implemented a rural medical internship program with the aims of preparing medical graduates for primary medical practice, and attracting them to rural areas. The purpose of this study was to understand the experience of medical interns in the rural medical internship program, and to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Better financial incentives were desired by doctors [ 52 , 54 , 56 , 58 , 60 , 73 , 74 , 85 87 ] and medical students to address rural doctor shortages [ 36 , 40 , 47 , 59 , 75 80 , 88 , 89 ] b) Opportunity to earn additional income ‡ Opportunity to additional income refers to income-generating activities related to clinical service, usually in private sector, hence the term ‘private practice’ Government doctors working in rural areas have a more limited opportunity for private practice [ 32 , 50 , 73 , 90 ]. While a study in Pakistan revealed that private practice was one of reasons of willingness to work in rural areas in Pakistan [ 45 ], a study in India discovered that aversion to private practice was among reasons of doctors chose to work in rural location [ 53 ] Lacking private practice opportunity in rural areas has discouraged interns to continue working in rural locations [ 80 ] D. Personal and professional support a) Better living conditions † Better living conditions refers to any environmental aspects related to personal amenity such as housing, transportation, electricity, water and communication, education and business facility Any general aspects of poor living conditions [ 45 , 50 , 52 , 57 , 72 , 83 ], schooling facilities [ 50 , 53 ], spouse employment [ 53 ], access to electricity and water supply [ 36 ], transportation [ 49 ], were among the key reasons for unwillingness to work rurally …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Better financial incentives were desired by doctors [ 52 , 54 , 56 , 58 , 60 , 73 , 74 , 85 87 ] and medical students to address rural doctor shortages [ 36 , 40 , 47 , 59 , 75 80 , 88 , 89 ] b) Opportunity to earn additional income ‡ Opportunity to additional income refers to income-generating activities related to clinical service, usually in private sector, hence the term ‘private practice’ Government doctors working in rural areas have a more limited opportunity for private practice [ 32 , 50 , 73 , 90 ]. While a study in Pakistan revealed that private practice was one of reasons of willingness to work in rural areas in Pakistan [ 45 ], a study in India discovered that aversion to private practice was among reasons of doctors chose to work in rural location [ 53 ] Lacking private practice opportunity in rural areas has discouraged interns to continue working in rural locations [ 80 ] D. Personal and professional support a) Better living conditions † Better living conditions refers to any environmental aspects related to personal amenity such as housing, transportation, electricity, water and communication, education and business facility Any general aspects of poor living conditions [ 45 , 50 , 52 , 57 , 72 , 83 ], schooling facilities [ 50 , 53 ], spouse employment [ 53 ], access to electricity and water supply [ 36 ], transportation [ 49 ], were among the key reasons for unwillingness to work rurally …”
Section: Resultsmentioning
confidence: 99%
“…Females regarded housing provision higher than males [ 58 , 74 ] b) Safe and supportive working environment† Working environment comprising both human and non-human resource such as: other health or non-health professionals, facility infrastructure, drugs and medical equipment Despite the same average working hours in their main job, doctors in rural areas had longer working hours in dual practice compared to urban doctors [ 46 ]. Higher rural doctors’ workloads, owing to inadequate supply of health professionals in rural location or difficult geographical access, was another reason doctors were unwilling to work or remain in rural posts [ 50 , 52 , 57 , 70 , 93 ] Other important attributes for rural doctor recruitment was lack of drugs, equipment and facility infrastructure [ 52 , 57 , 66 , 83 ], while for retention was good relationships with peer and manager [ 53 , 72 ] One study found that higher satisfaction score to work environment were associated with intention to stay working in rural area [ 91 ] Other attributes important to improve intention to work or staying in rural areas were: adequate number of health professional [ 73 , 85 ], relationship with colleagues or seniors [ 80 ], lack of drugs, equipment and poor facility infrastructure [ 40 , 59 , 60 , 73 , 79 , 81 , 88 , 92 , 94 ] Of those studies applying discrete choice experiment methods, 2 studies found that an adequate health facility was less important to medical students than salary [ 75 , 76 ], while 2 studies found the opposite among doctors [ 56 , 58 ] c) Foster interaction between urban and rural health workers† Interaction between urban and rural health workers comprising communication or consultation of docto...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations